Turn-Taking Analysis Strategies Used in Istighotsah Universitas Nadhlatul Ulama Surabaya - Savira Zaniar (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The "istighotsah" activities from UNUSA becomes one of routine activities every week on Thursday afternoon to "knock on heaven's door" through a series of prayers and dzikir together. It can be a communicative meeting to refresh our soul and also strengthen the silaturahim both for UNUSA academic community and others NU members.The goal of this study is to determine the sorts of turn taking methods, how those strategies were used, and which tactics were more frequently used by host, presenter and audience members at recent UNUSA sessions in "istighotsah." The data was collected from Zoom recordings of five recent “istgighotsah” UNUSA meeting. Turn taking strategies were selected and categorized in accordance with the Stenstrom theory of turn taking strategies during analysis of the data. All three of Stenstrom's turn taking tactics (taking, holding, and yielding) were found to be effective in the interactions of the host, presenter and audiences in those five recordings of “istighotsah” UNUSA. These tactics/strategies were used to interrupt the host and presenter in order to arrange the timing and topic of the conversation, explain or ask something relevant to the host and presenter, hold the turn and keep talking, encourage the audience to react, and give the audience the signal to take turn and begin speaking. According to Stenstrom's theory (1994), the most commonly employed strategy in the data was taking the turn strategy, as indicated by this study. Conversational analysis of turn-taking strategy may be supported by the findings here. Furthermore, the reader of this study, particularly from applied linguistics will find it useful as a resource of their study.